Private rental housing market underdevelopment: Life cycle model simulations for Poland - Michał Rubaszek (Baltic Journal of Economics, 2019)
The share of the private rental housing market in Central and Eastern European countries is low. With a survey data from Poland, I show that strong tenure preferences of households toward owning can be attributed to both economic and psychological factors. Building on these findings, I develop a life cycle model and I conduct counterfactual simulations to evaluate how changes in the structure of the rental market affect its size. I show that in the alternative scenario, which assumes (i) a change in the quality of rental services, (ii) lowering rental prices and (iii) diminishing fiscal incentives to own, the size of the private rental market is significantly higher, which leads to welfare gains for poor households.
Keywords: D91; E21; R21; 330; heterogenous agent model; Housing rental market; life cycle model; survey data